Aneurysm and Neurocysticercosis: Casual or Causal Relationship? Case Report and Review of the Literature - Svetlana Agapejev; João Luiz Parra-Marinello; Rodrigo Bazan; Anete Kinumi Ueda; Marco Antonio Zanini (Case Reports in Medicine)
Four cases of suggestive inflammatory aneurysms in patients with neurocysticercosis have been described. We report a case of a 49-year-old woman who presented with subarachnoid haemorrhage from a right middle cerebral artery bifurcation aneurysm and had a casual relationship with neurocysticercosis. At surgery, a viable cysticercus without signs of inflammation or thickened leptomeninges was found in the distal position of the aneurysm. Postoperatively, the patient received albendazole and dextrochlorpheniramine. In the subsequent three years, the patient was asymptomatic and took drugs to prevent convulsion and arterial hypertension. The relationship between NCC and the presence of cerebral aneurysm is discussed.